Money, Interest Rates and Prices in Ireland, 1933–2012. (December 2015) - Gerlach, Stefan; Stuart, Rebecca
In this paper we assemble an annual data set on broad and narrow money, prices, real economic activity and interest rates in Ireland from a variety of sources for the period 1933–2012. We discuss in detail how the data set is constructed and what assumptions we have made to do so. Furthermore, we estimate a simple SVAR model to provide some empirical evidence on the behaviour of these time series. Money supply shocks appear to be the most important drivers of both money and prices. Interest rate shocks, which capture monetary policy, play an important role driving output and, of course, interest rates. The real GDP shocks, which raise prices, seem of less importance.